Effect of chia (Salvia hispanica L.) on glucose metabolism, and their molecular mechanisms on insulin resistance conditions, in vivo and in vitro - Enes, Bárbara Nery (2020)
Chia (Salvia hispanica L.) is known for its high concentration of alpha linolenic acid omega 3, dietary fiber, proteins, vitamins, minerals and phytochemicals. These components are considered responsible for the improvement of biological markers related to non-communicable diseases. However, it is not clear whether there is an interaction between the compounds, or if a specific compound is responsible for the health benefits generated by the consumption of chia. In addition, the biochemical mechanisms and pathways involved in the chemoprevention of diseases caused by chia remain unknown. Therefore, the first investigations was, to compile evidence regarding the effects of chia seed (flour or oil) in studies with animals fed with unbalanced diets, and to understand the effects and molecular mechanisms in the modulation of metabolic biomarkers. Additional aims were to evaluate the influence of chia flour and oil on glucose metabolism in insulin-resistant Wistar rats, as well as to determine the effect of a phenolic extract from chia on glucose metabolism in insulin-resistant HepG2 cells. A systematic review was carried out on electronic databases, following the recommendations of PRISMA. The risk of bias and quality was assessed using the SYRILE toll and ARRIVE guidelines. The in vivo study was carried out with 40 male adults Wistar rats, initially divided into two groups: AIN-93M (n=10) and high fat and fructose content (HFHF) (n=30), during 8 weeks. Then, the HFHF group was divided into three groups (n=10): HFHF, HFHF with chia flour (14.7%) and HFHF with chia oil (4%). The parameters evaluated were: food consumption; adiposity; intraperitoneal tolerance to glucose and insulin; mRNA levels of enzymes and proteins involved on glucose metabolism (glycokinase, phosphofructokinase, pyruvate kinase, monophosphate-adenosine protein kinase, insulin receptor, protein transcription factor Forkhead box O1 and protein kinase B), as well as phosphorylated AKT (AKT1 [pS473]) protein level. The in vitro study was carried out with HepG2 cells, treated with glucose (25 mM) and palmitate (1mM) for 24 h, to induce insulin resistance. Insulin- resistant HepG2 cells were next, treated with hydrolyzed phenolics extract obtained from chia (20, 40 and 80 ppm). The hydrolyzed phenolics extract from chia were obtained by ultrasound liquid-liquid extraction, followed by hydrolysis with HCl (1 M). The characterization and quantification of phenolics from the hydrolyzed extract were assessed by reverse phase HPLC. To check effects from chia’s phenoliscs on insulin resistance, were analyzed the gene expression of AKT protein and enzymes involved in glycogenogenesis (phosphoenolpyruvate carboxykinase and glucose-6-phosphatase) and glycolysis (phosphofructokinase and pyruvate kinase). Throughout the 17 studies included in the systematic review, details on randomization and allocation concealment in studies were insufficient, as well as information on protocols. Among the studies, there was a lack of information about the sample size, the dose of chia used, and the number of animals evaluated for each parameter evaluated. However, summarizing the results, chia were associated with AMPK modulation, improment on glucose and insulin tolerance, lipogenesis, antioxidant activity and inflammation. The original in vivo study demonstrated that chia (seed and oil) increased AKT1 [pS473]. Chia oil improved glucose and insulin tolerance, increased AMPK, insulin receptor, FOX01, glycolysis enzymes and decreased gluconeogenesis enzymes. The in vitro experiment demonstrated that the phenolics of chia seeds decreased the expression of gluconeogenic enzymes without affecting the phosphorylation of AKT. Based on data from experimental studies, systematic review, chia presents bioactive potential and its daily consumption can reduce the risk of developing chronic diseases, mainly due to the antioxidant, antinflammatory, hypoglycemic and hypolipidemic effects of the seed. The original in vivo study indicated the potential of chia to improve glucose tolerance and positively affect insulin, neverthelesses, in vitro study showed that hydrolyzed phenolics from chia did not show effects. From the three fractions investigated in this research (flour, oil and hydrolyzed phenolics), the oil from chia demonstrated superior results regarding glucose metabolism in insulin resistance condition. Keywords: Chia flour. Chia oil. Alpha-linolenic acid. Phenolic compounds. AMPK. AKT.